LEGAL PROTECTION FOR CLEANING SERVICE WORKERS ON CAMPUS: AS SEEN IN THE FACE OF EMPLOYMENT LAW - Saputra, Angga Risqi; Isnawati; Farahwati; Ekawati (Awang Long Law Review, 2025)
This study aims to examine the form and extent of effectiveness of legal protection provided to cleaning service workers on campus from the perspective of the Manpower Law. Cleaning service workers play a crucial role in maintaining cleanliness and creating a comfortable atmosphere on campus, but their position is often vulnerable due to being tied to contract work systems or outsourcing mechanisms. This study uses a normative-empirical juridical approach, combining analysis of laws and regulations, legal theory and doctrine, and empirical findings obtained through interviews and field observations. The results show that, normatively, Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023, provides a strong basis for legal protection for workers, including outsourced workers. However, its implementation on campus has not been optimal. Various violations of workers' normative rights have been found, such as below-standard wages, lack of social security, violations of leave rights, and weak implementation of occupational safety and health (K3). The main factors contributing to weak legal protection include a lack of oversight by universities and the Department of Manpower, low legal awareness among workers and service providers, and a lack of internal complaint mechanisms within educational institutions. Effective legal protection not only ensures legal certainty but also realizes social justice and respect for human dignity, as embodied in the values of Pancasila and the ideals of national labor law.